Pembuatan Katoda Baterai Lithium Ion Iron Phospate (LiFePO4) dengan Metode Solid State Reaction - Elizabeth Putri Permatasari; Mega Permata Rindi; Agus Purwanto (Program studi Teknik Kimia UNS, 2017)
One of the most finest materials for lithium ion battery nowadays is lithium iron phosphate or LiFePO4. Lithium iron phosphate was synthesized with solid state reaction method by optimizing the variable of material and temperature. The variable for calcination temperatures were 700oC, 800oC, and 900oC while the basic materials as Fe sources were Fe2O3 and FeSO4. Particles morphologies and quantity of crystal were investigated in details by X-ray diffraction analysis XRD. XRD imaging showed diffraction of nanoparticles LiFePO4 with crystal quantity 40,4% (800oC) and 59,1% (900oC) of materials Fe2O3,which the most quantity from other samples. Thus, chatode materials were made from LiFePO4 that synthesized at calcination temperatures 800oC and 900oC. In conclusion the material chatode from LiFePO4 that had been synthesized had so many impurities because it was hard to get single phase of nanoparticles LiFePO4 and need more improvement in optimizing the process condition for ideal chatode material.